2008
DOI: 10.1097/mao.0b013e318184586d
|View full text |Cite
|
Sign up to set email alerts
|

Daily Exercise Does Not Prevent Recurrence of Benign Paroxysmal Positional Vertigo

Abstract: Our results suggest that a daily routine of the self-CRP does not affect the time to recurrence and the rate of recurrence of posterior canal-BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…Static and dynamic postural deficits are more severe in patients with posterior SCC-BPPV [18] and the assessment of instability at the time of diagnosis with a simple measure, as we have shown, will be of help to identify which patients would probably benefit from CRMs and home exercises for instability, a measure that has been demonstrated to be of no help if provided to a general population of patients with BPPV [19]. This measurement and its relevance are reinforced by the combined use of the CIEV score, which has a prognostic value according to its developers and first analysis [11].…”
Section: Discussionmentioning
confidence: 93%
“…Static and dynamic postural deficits are more severe in patients with posterior SCC-BPPV [18] and the assessment of instability at the time of diagnosis with a simple measure, as we have shown, will be of help to identify which patients would probably benefit from CRMs and home exercises for instability, a measure that has been demonstrated to be of no help if provided to a general population of patients with BPPV [19]. This measurement and its relevance are reinforced by the combined use of the CIEV score, which has a prognostic value according to its developers and first analysis [11].…”
Section: Discussionmentioning
confidence: 93%
“…The classifications of the BPPV subtypes such as posterior semicircular canal (PSCC)-type BPPV (P-BPPV), horizontal semicircular canal (HSCC)-type BPPV with geotropic positional nystagmus (GH-BPPV), HSCC-type BPPV with apogeotropic positional nystagmus (AH-BPPV) are well organized, and the treatments for each subtype of BPPVsuch as the canalith repositioning procedure (CRP)are well established [4]. There have been some studies on prevention of recurrence, and Helminski et al reported that daily exercise does not affect the time to recurrence or the rate of P-BPPV recurrence [5]. When we decide to treat patients with BPPV and decide on preventive measures, we have to diagnose the subtype and the affected ear by observation of positional and positioning nystagmus.…”
Section: Introductionmentioning
confidence: 99%
“…The third DHT (#3) was administered one month after the second DHT in all patients. If the DHT (#3) was still positive for nystagmus and vertigo, then a third PRM was given ( Figure 1) and defined as "recurrence of BPPV" (15). Subjective complaints measured using VAS, with "residual daily dizziness" defined as the sensation of unsteadiness or lightheadedness without rotational and/or positional vertigo.…”
Section: Treatment Methodsmentioning
confidence: 99%